Posttraumatic Stress Disorder Symptoms in Lymphoma Patients: A Prospective Study - Camille, Claire; Dimeglio, Chloé; Yrondi, Antoine; Compaci, Gisèle; Delmas, Emmanuelle; Gauché, Mélanie; Laurent, Guy; Birmes, Philippe (Frontiers in Psychiatry, 2020)
The cancer experience may be marked by repeat stressors and/or traumas. The aim of our study was to assess traumatic events in a group of patients diagnosed with lymphoma and to determine which of these contribute to the development of Post-Traumatic Stress Disorder/PTSD. Two weeks after receiving a diagnosis of lymphoma, patients were referred for an assessment of peritraumatic distress (using the Peritraumatic Distress Inventory/PDI) and peritraumatic dissociation (using the Peritraumatic Dissociative Experiences Questionnaire/PDEQ). Three months after the diagnosis, we recorded the following parameters: the patients' worst experiences, the presence of PTSD symptoms, using the PTSD CheckList/PCL, as it related to the diagnosis, and symptoms of anxiety using the Hospital Anxiety and Depression/HAD scale and of depression using the Beck Depression Inventory/BDI-II. The study recruited 129 patients, with a mean age of 46 years (SD = 17.3); 70 (54%) men, 87 (67.5%) with Non-Hodgkin's lymphoma, and 42 with Hodgkin's lymphoma. Two weeks after the diagnosis, 49% of patients reported peritraumatic distress, and 20% peritraumatic dissociation, during or immediately after being informed of the lymphoma diagnosis. Three months after the diagnosis, the severity of PTSD symptoms was evaluated. At this stage none of the patients suffered PTSD, but 29 (23%) individuals exhibited partial PTSD: 13.4% correlated it to receiving the lymphoma diagnosis, 8% to telling family members, and 1.6% to adverse effects. Peritraumatic distress and dissociation as a result of receiving a lymphoma diagnosis, as well as anxiety and a mucositis within the first 3 months post-diagnosis, were factors that were significantly associated with PTSD symptoms, accounting for 35.8% in PTSD symptom load. Our study reveals that clinicians should assess the impact of a number of stressors, which are risk factors for PTSD symptoms, starting from the time point of the initial lymphoma diagnosis.